2021
DOI: 10.1002/ppap.202100077
|View full text |Cite
|
Sign up to set email alerts
|

Efficient trapping of RONS in gelatin and physiological solutions

Abstract: The work aims to determine the long‐term stability of reactive oxygen and nitrogen species (RONS)‐enriched gelatin solutions and of plasma‐activated physiological solutions produced with an atmospheric pressure surface‐wave microwave discharge. It is demonstrated that the H 2 O 2 , NO 3 −, and NO 2 − concentrations are quasi‐stable during 1 month of storage in the 0.5%–2% gelatin solutions prepared with plasma‐activated water, Ringer's (PAR), and phosphate‐buffered saline (PAPBS) solutions, respectively, eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The beaker is placed on a magnetic stirrer (IKA lab disc) and positioned below the plasma plume with the water surface being at distance d $d$ from the edge of the quartz tube as already presented in Kutasi and Tomacz. [ 1 ] At the water contact, the plasma streamers cover a 6 mm diameter circular area. The stirring speed is set to 60–100 rpm.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beaker is placed on a magnetic stirrer (IKA lab disc) and positioned below the plasma plume with the water surface being at distance d $d$ from the edge of the quartz tube as already presented in Kutasi and Tomacz. [ 1 ] At the water contact, the plasma streamers cover a 6 mm diameter circular area. The stirring speed is set to 60–100 rpm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In the last decade, it has been demonstrated that the RONS deposited into liquids can have antitumor/cancer, antibacterial and antimicrobial effect, and can induce oxidative stress to cells. An overview of the demonstrating studies has been given in Ref., [ 1,2 ] which indicate that the main role is played by the long‐lived RONS either directly or indirectly. The disinfecting property of PAL has been attributed to the synergistic effect of different RONS, [ 3,4 ] while in several studies, the emphasize is given to the pH of the solution or/and the peroxynitrite, peroxynitrous acid (ONOOH) and peroxynitric acid (O2 ${{\rm{O}}}_{2}$NOOH), which are created from the reaction of H2O2 ${{\rm{H}}}_{2}{{\rm{O}}}_{2}$ with NO2 ${\text{NO}}_{2}^{-}$ under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, PAW is produced by the plasma treatment of water alone, so the sterilization activity of PAW is relatively lower than that of PA-AVC. Meanwhile, PAW will lose its sterilization effect after a short period of time, while the network of PAH can restore the reactive species in solution, reducing the loss of their mutual reaction activity and prolonging the antimicrobial activity [35,37] and making it a more effective and practical microbial disinfection treatment (Figure 5a). Using the electron spin resonance (ESR) spectrometer and the enzyme marker, we measured the contents of ONOO − It is worth mentioning that although the PAHs were prepared from the mixing of PAW and dry gel powder, the concentration of short-lived reactive species in the PAHs was lower than that of PAW.…”
Section: Discussionmentioning
confidence: 99%
“…It is presumed that this is because AVC hydrogels have hydrophilic groups such as ammonium groups, which dissolve into gel-like dispersions in aqueous solutions (PAW) with a unique spatial structure, when the droplets are covered by fully adsorbed polymer molecules and the reactive species are separated from each other and from external reducing substances, thus reducing their consumption during storage and prolonging the antimicrobial activity. [36][37][38]55] In order to further discuss the correlation between the pH and ORP of PAHs and their antibacterial activities, the activation time for the PAH preparation was extended to maintain their pH and ORP values at a similar level (Figure 2e 2 indicate that the antibacterial activity of PAHs was directly related to the plasma-generated species stored in hydrogels rather than their pH and ORP values.…”
Section: Sterilization Comparison Between Paw and Pahmentioning
confidence: 99%
See 1 more Smart Citation